Answer:
p(x - 4) = x³ - 12x² + 48x - 69
Step-by-step explanation:
To evaluate p(x - 4), substitute a = x - 4 into p(a), that is
p(x - 4) = (x - 4)³ - 5
= (x - 4)(x - 4)(x - 4) - 5 ← expand 2nd/ 3rd factors using FOIL
= (x - 4)(x² - 8x + 16) - 5 ← distribute parenthesis
= x³ - 8x² + 16x - 4x² + 32x - 64 - 5 ← collect like terms
= x³ - 12x² + 48x - 69
Is the 2 a exponent?
If it is the answer is for that:
-3x^2+12x
=3x(-x+4)
=3x(-x+4)
Answer:
10 + (-14) = -4
Step-by-step explanation:
Given that,
Diamond used a number line to add. She started counting at 10, and then she counted until she was on the number −4 on the number line.
For addition, she will add 10 and (-14) as follows :
10 + (-14) = -4
So, the crrect option is (b) "10 + (-14) = -4".
Answer:
M < abc = 55 Degrees
Step-by-step explanation:
Since you can use the substitute angle of the triangle, this enables you to simplify the equation, knowing that all triangles angles add up to 180 degrees.